Effect of intravenous fluid supplementation in healthy term neonates with non-hemolytic hyperbilirubinemia: A randomized controlled trial - Sarvi, Meenakshi; Patil, Shailesh S; Desai, Arunkumar (Indian Journal of Child Health, 2018)
Objective: The objective of this study was to evaluate the effect of intravenous fluid supplementation in healthy term neonates with non-hemolytic hyperbilirubinemia receiving phototherapy. Study Design: Randomized controlled trial conducted in a tertiary level neonatal care unit of a teaching institute in North Karnataka. Methods: A total of 60 healthy term neonates with non-hemolytic hyperbilirubinemia (total serum bilirubin [TSB] >15 mg/dL [256 ?mol/L]–<25 mg/dL [428 ?mol/L]) were randomized to two groups. Group I (case group, n=30) received 1/3rd the maintenance intravenous fluid in addition to breastfeeding and phototherapy. Group II (control group, n=30) received only breastfeeding and phototherapy. The duration of phototherapy and rate of fall of bilirubin was compared. Results: Both the groups were comparable with respect to mean birth weight, gestational age, gender, mode of delivery, age at admission, admission weight, percentage of weight loss at admission, and TSB at inclusion. There was a significant difference in the duration of phototherapy between the two groups (mean [standard deviation (SD)] Group I, 39.6 [7.8] h and Group II, 45.2 [10.22] h, p<0.05). Percentage of fall in bilirubin was not significant at 4, 12, 48, and 60 h but was significant at 24 and 36 h. Conclusion: Intravenous fluid supplementation in healthy breastfed term neonates with non-hemolytic hyperbilirubinemia significantly reduces the duration of phototherapy.